Gastroenterological disorders in inborn errors of immunity. Part 2 A. Overview of selected diseases - Napiórkowska-Baran, Katarzyna; Treichel, Paweł; Koperska, Kinga; Kudrej, Oliwia; Mućka, Natalia; Rajewska, Alicja; Wawrzeńczyk, Adam; Bartuzi, Zbigniew (Gastroenterology Review/Przegląd Gastroenterologiczny, 2026)
Gastrointestinal symptoms are common in patients with inborn errors of immunity and may serve as early indicators of immunological dysregulation. This review focuses on selected diseases of the IUIS classification, where gastrointestinal manifestations play a crucial role. The analysis is based on a wide range of scientific literature addressing clinical, diagnostic, and therapeutic aspects, emphasising the need for a multidisciplinary approach in patient management.